Crop Depredation by Monkey Outside Protected Area in Nepal; Costs, Conditions and Perceptions - Paudel, Ganesh; Shrestha, Tej Kumar (Indian Forester, 2018)
Human wildlife conflict outside the protected area is increasing in Nepal however; government and their conservation partners are mainly focused in biodiversity issues within protected areas only. This study was conducted in Jaidi village of Baglung district to analyze the status of crop damage and people's perception on such damage caused by monkey. Data were collected through series of community consultation, field observation and household survey at 10% sampling intensity. The annual crop damage in volume and cost was 183.46 kg/HH and NRs 7659.77/HH respectively. Amount of damage was significantly different with different varieties of crops (p=0.000). Multiple linear regressions showed that amount of crop was significantly dependent on the distance of farm from the forest area (ß= -0.052, p= 0.000), available water source (ß= -0.059, p= 0.000), respondents house (ß= 0.021, p= 0.000), and nearby settlement (ß= 0.038, p= 0.000). More than half of the respondents were unwilling to conserve monkey due to damage caused to their crops. The willingness to monkey conservation and the extent of damage are found to be dependent. This study recommends to formulate the human monkey management plan outside the protected area.